2004
DOI: 10.1002/eat.20013
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and gender identity disorder in biologic males: A report of two cases

Abstract: Differences between the two cases are discussed. Issues of gender identity should be considered in the assessment of male patients presenting with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
(13 reference statements)
3
29
1
Order By: Relevance
“…The present population-based sample consisted of 1,142 participants of both genders, whose age ranged from 18 to 44 years. Confirming previous research and our hypotheses, an association between gender identity conflict and body dissatisfaction (Bozkurt et al 2006;Strong et al 2000;Vocks et al 2009) as well as disordered eating (Hepp and Milos 2002;Silverstein et al 1990;Vocks et al 2009;Winston et al 2004) was detected. Both biological males and females with a conflicted gender identity consistently showed higher levels of body dissatisfaction than controls, and biological females with a conflicted gender identity also showed higher levels of disordered eating.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present population-based sample consisted of 1,142 participants of both genders, whose age ranged from 18 to 44 years. Confirming previous research and our hypotheses, an association between gender identity conflict and body dissatisfaction (Bozkurt et al 2006;Strong et al 2000;Vocks et al 2009) as well as disordered eating (Hepp and Milos 2002;Silverstein et al 1990;Vocks et al 2009;Winston et al 2004) was detected. Both biological males and females with a conflicted gender identity consistently showed higher levels of body dissatisfaction than controls, and biological females with a conflicted gender identity also showed higher levels of disordered eating.…”
Section: Discussionsupporting
confidence: 92%
“…Male-to-female transsexuals showed more restrained eating, concerns about eating, weight and shape, drive for thinness, bulimic behavior, body dissatisfaction, and body checking than male controls, and higher degrees of weight and shape concerns, body dissatisfaction, and body checking than female controls. Based on case reports and clinical experience from Spain, Switzerland and the United Kingdom, gender identity disorder has likewise been associated with an increased risk for eating disorders for both biological males and females (Fernández-Aranda et al 2000;Hepp and Milos 2002;Winston et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, research has investigated the development of eating disorders and disturbances in overall identity impairment (Schupak-Neuberg & Nemeroff, 1993;Stein & Corte, 2007;Weinreich, Doherty, & Harris, 1985); gender identity disorder (Hepp & Milos, 2002;Winston, Acharya, Chaudhuri, & Fellowes, 2004) and feminist identity (Green, Scott, Riopel, & Skaggs, 2008;Sabik & Tylka, 2006;Sitnick & Katz, 1984;Snyder & Hasbrouck, 1996;Timko, Striegel-Moore, Silberstein, & Rodin, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Winston et al (2004) have reported two cases of anorexia nervosa and gender identity disorder in biological males who accessed to an eating disorders service. Vocks et al (2008) have carried out one of the few existing studies (on a moderate sample size), to our knowledge, to discover whether individuals with a gender identity disorder (88 male-to-female transsexuals and 43 female-to-male transsexuals) differ from controls of both sexes (56 males and 116 female) and from eating-disordered individuals (62 females) in terms of eating and body image disturbances.…”
Section: Eating Disorders and Gender Identity Disordersmentioning
confidence: 99%